Service Quality Analysis of the Regional Drinking Water Company (PDAM) Tirta Sejuk Against the Need for Clean Water in Blangkejeren - Ali, Khaidir; Rizky, Rafieqah Nalar; Ulayya, Atikah (PERSPEKTIF, 2024)
One of the BUMDs owned by the regional government is The Regional Drinking Water Company (PDAM), which is responsible for developing and managing a clean water supply system to serve consumers at more affordable prices. The need for clean water is something that is of great concern because it is one of the primary human needs that cannot be avoided in everyday life. This research aims to determine the analysis of the service quality of PDAM Tirta Sejuk regarding the need for clean water in Blangkejeren. The method used is a qualitative method with descriptive analysis to obtain a systematic, factual and accurate picture of the problems studied. This research also uses Zeithaml's theory which consists of several main indicators, namely: tangibles, empathy, responsiveness, reliability and guarantee. The results of the research show that the service provided to consumers is quite good and satisfying, seen in its form, namely the existence of facilities and infrastructure to support service quality and meet community needs, prioritizing good communication in creating a sense of empathy for customers, and responsiveness in overcoming various problems that occur regarding clean water needs. Apart from that, reliability is also emphasized to fulfill promises of guarantees that will be given to customers.